Introduction - Sablina, Ivan; Bender De Moniz Bandeira, Egas Bernard (Parliaments, Elections and Constitutions in Qing and Russian Imperial Transformations, 1860s-1920s, 2022)
This special issue explores concepts and practices related to parliamentarism in the imperial and post-imperial transformations of the Qing and Russian Empires, as well as their successor states. It demonstrates that representative institutions were a crucial factor in the establishment of modernized empires or post-imperial states. In particular, the issue explores how the ‘mining’ of own imperial past and present for concepts and practices was used in combination with the globally circulating forms of representation in the development of parliamentary institutions, how particular interest groups defined through ethnicity, region, religion, or class were represented, and, ultimately, how the parliamentary developments informed the formation of single-party regimes in the post-imperial settings.<br
Keywords: Russia; China; Qing; Soviet; parliament; diversity